2022
DOI: 10.1007/jhep03(2022)173
|View full text |Cite
|
Sign up to set email alerts
|

On type 0 string theory in solvable RR backgrounds

Abstract: Motivated by a possibility of solving non-supersymmetric type 0 string theory in AdS5× S5 background using integrability, we revisit the construction of type 0 string spectrum in some solvable examples of backgrounds with RR fluxes that are common to type IIB and type 0B theories. The presence of RR fluxes requires the use of a Green-Schwarz description for type 0 string theory. Like in flat space, the spectrum of type 0 theory can be derived from the type II theory spectrum by a (−1)F orbifolding, i.e. combin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…which is the lowest energy mode of the twisted sector in the GS string construction [48,49]. In [53] it was suggested that on the AdS 5 × S 5 background with 5-form flux F 5 the tachyon may get stabilised, with some further evidence provided in [51]. There, we analysed the type 0B string on the pp-wave background that arises in the BMN-limit (J, g → ∞ with J = J g fixed) of AdS 5 × S 5 .…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 3 more Smart Citations
“…which is the lowest energy mode of the twisted sector in the GS string construction [48,49]. In [53] it was suggested that on the AdS 5 × S 5 background with 5-form flux F 5 the tachyon may get stabilised, with some further evidence provided in [51]. There, we analysed the type 0B string on the pp-wave background that arises in the BMN-limit (J, g → ∞ with J = J g fixed) of AdS 5 × S 5 .…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…We can also study type 0 string theory on non-trivial curved and/or fluxed Type II backgrounds, if we find a way to perform a similar orbifolding. In [50,51] an explicit construction using a continuous deformation called Melvin-twist was investigated and applied to pp-wave backgrounds. For AdS 5 × S 5 we can use the large amount of symmetry and perform the necessary orbifolding using the techniques we presented above.…”
Section: Type 0b String On Ads 5 × Smentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the discussion above is focused on the torus partition function, and it would be interesting to generalize it to non-orientable manifolds. That would allow us to study integrable worldsheet theories for unoriented type 0 string (see [80] for a related discussion), for which the existence of eight different GSO projections was pointed out recently [81,82].…”
Section: Fermionization Of Integrable Field Theoriesmentioning
confidence: 99%